Sobre la noción de Derecho Natural en Graciano - Martínez Martínez, Faustino (FORO. Revista de Ciencias Jurídicas y Sociales, Nueva Época, 2004)
Starting by the analysis of S Isidoro’s thought, main intellectual source in legal knowledge during all the first centuries of Middle Ages, this work tries to examine the concept of Natural Law employed by Gratianus in his main compilatory work (the Decretum). We intend to remark the three senses of a word, the triple notion of Natural Law, a Natural Law that in XII century is in half-way between the augustinist voluntarism and the racionalist revolution, an aristothelic revolution that is coming.